Hubungan Pengetahuan Dan Pendidikan Ibu Hamil dengan Kepatuhan Kunjungan Antenatal Care (ANC) di Puskesmas Wawonasa Kota Manado - Megawati Husna Laiya; Zainar Kasim; Endang Puji Ati (Jurnal Ners, 2026)
Antenatal care is health services provided by professionals to mothers during pregnancy in accordance with established antenatal care service standards. Antenatal care can detect high risks to pregnancy and childbirth early on, reduce maternal mortality rates, and monitor fetal development. Antenatal care services in Indonesia have increased significantly over a period of approximately four years in terms of four antenatal care visits (K4). In 2018, approximately 74.1% of pregnant women underwent antenatal care examinations with complete visits (K4). In 2021, there was an increase of approximately 88.13% in pregnant women undergoing antenatal care examinations. The indicator for pregnancy visits increased to around 85%. The purpose of this study was to determine the level of knowledge and education of pregnant women with regard to compliance with antenatal care visits at the Wawonasa Community Health Center in Manado City. The method used was quantitative research with a correlational design using a cross-sectional approach and the chi-square test. The statistical test results showed a p-value of 0.000. This indicates that p ≤ 0.05, so Ha is accepted and H0 is rejected, leading to the conclusion that there is a relationship between the knowledge and education of pregnant women and their compliance with antenatal care (ANC) visits at the Wawonasa Community Health Center in Manado City.